The role of ketogenesis in the migratory fattening of the northern wheatear Oenanthe oenanthe - Frias Soler, Roberto Carlos; Kelsey, Natalie A.; Villarín Pildaín, Lilian; Wink, Michael; Bairlein, Franz (Biology letters, 2021)
The fuelling capacity of migratory birds and their ability to avoid health conditions derived from the subsequent fat overload are exceptional among vertebrates. In this work, we screen the expression of the genes involved in the production of ketone bodies (KB) in the liver of northern wheatears (Oenanthe oenanthe) during the development and resolution of migratory fattening. Thirteen genes were found to be regulated among the migratory stages. Based on the dynamics of gene expression, we concluded that KB play a versatile role in wheatears' energy metabolism homeostasis. The ketogenic pathway can adaptively: (i) provide carbon equivalents for lipogenesis, speeding up fuelling; (ii) replace glucose during long-distance flights using lipids as the substrate; (iii) act as a floodgate to avoid steatosis; and (iv) might provide a metabolic solution to defatting in captive birds.